Self-Care is Associated with Quality of Life in Chronic Kidney Disease Undergoing Hemodialysis Self-Care Dihubungkan dengan Kualitas Hidup pada Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Rosyid, Fahrun Nur; Sugiharto, Sh; Dhani, Sheena Ramadhia Asmara; Vera, Lenia Septika; Safitri, Lisa Novia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
ABSTRACT Chronic Kidney Disease (CKD) significantly affects the quality of life of patients, often due to limitations in their ability to care for themselves. Effective self-care is crucial in managing CKD, as it directly affects daily routines and overall well-being. The aim of this study is to assess the relationship between self-care and the quality of life of CKD patients undergoing hemodialysis treatment. A quantitative, cross-sectional approach was used, involving 91 participants selected through accidental sampling. Data were collected using the "Chronic Kidney Disease Self-Care Index" and the "WHOQOL-BREF" questionnaire to evaluate self-care and quality of life. Chi-Square analysis at p 0.05 revealed a significant correlation between self-care and quality of life (p = 0.001). The study results indicate that 1.1% of participants are fully dependent on self-care, 61.5% are partially dependent, and 37.4% are independent. Specifically, all independent participants reported a good quality of life, while no participants were fully dependent. These findings underscore the importance of promoting self-care practices among CKD patients to improve their quality of life. Healthcare professionals are encouraged to provide support, motivation, and targeted guidance to foster self-care behaviors in this population. ABSTRAK Penyakit Ginjal Kronis (PGK) secara signifikan memengaruhi kualitas hidup pasien, sering kali karena keterbatasan kemampuan merawat diri sendiri. Perawatan diri yang efektif sangat penting dalam mengelola PGK, karena secara langsung memengaruhi rutinitas harian dan kesejahteraan secara keseluruhan. Tujuan penelitian ini adalah untuk menilai hubungan perawatan diri dengan kualitas hidup pasien PGK yang menjalani perawatan hemodialisis. Pendekatan kuantitatif, cross-sectional digunakan, yang melibatkan 91 peserta yang dipilih melalui metode accidental sampling. Data dikumpulkan menggunakan "Indeks Perawatan Diri Pasien Ginjal Kronis" dan survei "WHOQOL-BREF" untuk mengevaluasi perawatan diri dan kualitas hidup. Analisis Chi-Square pada p 0,05 mengungkapkan korelasi yang signifikan antara perawatan diri dan kualitas hidup (p = 0,001). Hasil penelitian menunjukkan bahwa 1,1% peserta sepenuhnya bergantung pada perawatan diri, 61,5% sebagian bergantung, dan 37,4% mandiri. Khususnya, semua peserta mandiri melaporkan kualitas hidup yang baik, sementara tidak ada peserta yang sepenuhnya bergantung. Temuan ini menggarisbawahi pentingnya mempromosikan praktik perawatan diri di antara pasien CKD untuk meningkatkan kualitas hidup mereka. Para profesional perawatan kesehatan didorong untuk memberikan dukungan, motivasi, dan bimbingan yang terarah untuk menumbuhkan perilaku perawatan diri pada populasi ini.